Genetic analysis of axon guidance mechanisms during ambryonic development of Drosophila melanogaster using DNA microarrays - Magalhães, Luís Tiago Ferreira Romero (2007)
Tese de doutoramento em Biologia (Biologia Celular) apresentada à Fac. de Ciências e Tecnologia de Coimbra